Systems Social Marketing and Macro-Social Marketing: A Systematic Review. (June 2020) - Flaherty, Tina; Domegan, Christine; Duane, Sinead; Brychkov, Dmitry; Anand, Mihir
Background: The adoption of systems thinking within social marketing is illustrated by the emerging literature relating to systems social marketing and macro-social marketing. Systems social marketing and macro-social marketing signal a shift from singular level behavior change toward a more holistic, multilevel change mode of operandi for complex and wicked problems. In recognition of this broadening perspective, Truong et al. took the first steps to describe the relationship between systems thinking and social marketing through a critical appraisal. However, their analysis stopped short of defining systems social marketing and macro-social marketing, examining how the concepts have been applied, and the impact this has on our change methodologies. Focus: This article is related to research and evaluation of the social marketing field. Research Question: This study aims to (a) examine the causality looseness surrounding the descriptions of systems social marketing and macro-social marketing, (b) conceptualize systems social marketing and macro-social marketing, and (c) develop a taxonomy for classifying and interpreting the systems-based social marketing–related literature. Methods: Following best practice protocols, a systematic review was conducted to identify systems social marketing and macro-social marketing literature and interventions published prior to March 2020. Five databases were searched using a combination of relevant search terms. Results: Sixteen thousand and forty-seven title and abstracts were screened, resulting in 45 articles being reviewed, 8 of which were interventions. Analysis of the findings indicated both systems social marketing and macro-social marketing use nonlinear causality and seeks to understand the structural and behavioral dynamics in a system to leverage change. Moreover, the findings suggest that systems social marketing focuses on evolutionary dynamics and a "whole system in the room" approach, pursuing top-down, bottom-up iterative processes with macro-social marketing pursuing institutional dynamics and "inside the system" top-down processes. Importance to Social Marketing Field: This article is one of the first efforts to examine the inner anatomy of systems social marketing and macro-social marketing for causality and definitional clarity. In drawing a distinction between the two orientations, social marketers can begin to understand in what contexts and settings these perspectives are most applicable. Recommendations: The taxonomy and search strategy can be adopted in other reviews as they offer a rich and diverse basis for further conceptual analysis of systems-based social marketing–related literature. Limitation: Community-based prevention marketing, community-based social marketing, and community-led assets-based social marketing articles were excluded from this review. Hence, further research could include these approaches and uncover their features, analogies, and differences versus systems social marketing and macro-social marketing.